Changes in Students Social Justice and Racial Attitudes in an Undergraduate Child Psychology Service-Learning Course - Fenzel, Ph.D., L. Mickey; Dean, Rebecca (International Journal of Research on Service-Learning in Teacher Education, 2011)
This study examines changes in students perceptions of the existence of White privilege and racism and their personal social justice commitment during the course of a semester. Participants included 93 Caucasian undergraduates enrolled in a course in child development that had a required service-learning component. Outcomes are examined using pencil-and-paper pre- and post-test assessments and web-based end-of-course evaluations. Results showed consistent gains in students perceptions of the importance that society takes steps to care for persons who are disadvantaged and that society takes greater action to improve the education of urban children placed at risk. Pre- to post-test gains in students awareness of White privilege and the existence of racism and their commitment to social justice were also noted. Findings are discussed in light of the kinds of reflection activities in which students participated during and outside of class time.